Strategies of Successful English Language Learners among Private School Students - Stella Ang; Mohamed Amin Embi; Melor Md. Yunus (Jurnal Pendidikan Humaniora, 2017)
Abstract: In general, language learners depict different ability and grasp of learning the language. Due to the fact that individual learns differently, researchers are interested to study how English language learners learn the language successfully. This study is designed to identify the area of language learning strategies that were employed by ten successful English Language Learners of Form Five from a private secondary school in Kuching, Sarawak. The strategies used by these learners help promote and boost the use of strategies among poor language learners. Using a purposive sampling procedure, a group comprising of ten successful language learners of a private school in Kuching, Sarawak participated in the study. The findings indicated that successful language learners are high frequency users of language learning strategies. The findings revealed that metacognitive strategies are among the highest frequently used strategies, followed correspondingly by social, cognitive, compensation, affective and memory strategies found as the least used strategies among successful language learners. The total means of each category showed that metacognitive strategies (Mean=4.466) are among the most frequently used strategies, followed respectively by social (Mean=4.217), cognitive (Mean=4.036), compensation (Mean=3.450), affective (Mean=3.233) and memory strategies (Mean=2.867) found as the least used strategies among successful language learners. Interestingly, the study acknowledged that successful language learners employed more indirect strategies paralleled to direct strategies. The findings have significant implications for research on language learning strategies concerning successful language learners and teacher planning to cater the needs of diverse learners in English Language and improve the field of language teaching.Key Words: language learning strategies, successful language learners, english as a second language Abstrak: Secara umum, pebelajar bahasa menggambarkan kemampuan dan pemahaman pembelajaran bahasa yang berbeda. Karena pada kenyataannya individu memiliki cara belajar yang berbeda, peneliti tertarik untuk mempelajari bagaimana pebelajar Bahasa Inggris belajar bahasa dengan sukses. Penelitian ini dirancang untuk mengidentifikasi area strategi pembelajaran bahasa yang digunakan oleh sepuluh pebelajar Bahasa Inggris yang berhasil di lima sekolah menengah swasta di Kuching, Sarawak. Strategi yang digunakan oleh pebelajar ini membantu untuk mempromosikan dan meningkatkan penggunaan strategi di antara pebelajar dengan Bahasa yang dianggap kurang. Dengan menggunakan prosedur purposive sampling, sekelompok yang terdiri dari sepuluh pebelajar bahasa yang berhasil belajar di sebuah sekolah swasta di Kuching, Sarawak berpartisipasi dalam penelitian ini. Temuan penelitian ini menunjukkan bahwa pebelajar bahasa yang berhasil adalah pebelajar yang menggunakan strategi pembelajaran bahasa frekuensi tinggi. Temuan tersebut mengungkapkan bahwa strategi metakognitif adalah strategi yang paling sering digunakan, diikuti oleh strategi sosial, kognitif, kompensasi, afektif dan memori yang ditemukan sebagai strategi yang paling sedikit digunakan di antara pelajar bahasa yang berhasil. Total mean dari masing-masing kategori menunjukkan bahwa strategi metakognitif (Mean = 4.466) adalah salah satu strategi yang paling sering digunakan, diikuti masing-masing oleh sosial (Mean = 4,217), kognitif (Mean = 4,036), kompensasi (Mean = 3,450), afektif (Mean = 3.233) dan strategi memori (Mean = 2.867) ditemukan sebagai strategi yang paling sedikit digunakan di antara pebelajar bahasa yang berhasil. Menariknya, penelitian ini mengakui bahwa pebelajar bahasa yang sukses menggunakan lebih banyak strategi tidak langsung yang sejalan dengan strategi langsung. Temuan ini memiliki implikasi yang signifikan terhadap penelitian tentang strategi pembelajaran bahasa mengenai pebelajar bahasa yang berhasil dan perencanaan guru untuk memenuhi kebutuhan pebelajar yang beragam dalam Bahasa Inggris dan memperbaiki bidang pengajaran bahasa.Kata kunci: strategi belajar bahasa, pebelajar bahasa yang sukses, ahasa inggris sebagai bahasa kedua